Peningkatan Ketersediaan dan Serapan P pada Tanaman Jagung Di Lahan Tercemar Limbah Padat Kapur (Lime Mud) Melalui Penambahan Bahan Organik - Tiara Rizky Oceananda Suharto; Tri Candra Setiawati; Sugeng Winarso (Program Studi Agroteknologi Fakultas Pertanian Universitas Andalas, 2018)
The soil contaminated by lime mud has a high content of Ca and Na. It affects the availability of nutrients within the soil. Calcareous soil conditions tend to disperse, sensitive to washing and erosion. Meanwhile, the availability of P nutrients is also low due to the binding of P by Ca in the form of (Ca3PO4)2 that leads the soil productivity to be low. Organic material is a soil enhancer which has complete function, easily available, abundant and can increase P nutrients especially for the plants in the long-term. Hence, the objective of this research was to observe the response of increasing level of soil P contaminated by lime mud and P uptake in maize plant tissues toward the treatment of adding organic material. The research design used in this study was factorial randomized block design comprising of two factors and three replications. The first factor was the source of fertilizer (1) no fertilizer (P0), (2) animal waste bokashi (P1), (3) straw bokashi (P2), (4) guano organic (P3), and (5) NPK inorganic (P4). The second factor was (1) polluted soil (T1) and (2) unpolluted soil (T2). The results revealed that combination of fertilizer types and planting media could significantly increase soil Ca and wet weight of maize crops, additionally gave impact indirectly toward soil pH, P and C-Organic content in the soil, P uptake, plant height, root volume, and dry weight of maize crops. By doing a treatment of giving animal waste bokashi fertilizer combined with contaminated soil media, it apparently produced better results than controlling, and resulted better product than treating them with straw bokashi fertilizer and guano organic fertilizer.